2009
DOI: 10.1073/pnas.0810595106
|View full text |Cite|
|
Sign up to set email alerts
|

S-nitrosylation of XIAP compromises neuronal survival in Parkinson's disease

Abstract: Inhibitors of apoptosis (IAPs) are a family of highly-conserved proteins that regulate cell survival through binding to caspases, the final executioners of apoptosis. X-linked IAP (XIAP) is the most widely expressed IAP and plays an important function in regulating cell survival. XIAP contains 3 baculoviral IAP repeats (BIRs) followed by a RING finger domain at the C terminal. The BIR domains of XIAP possess anticaspase activities, whereas the RING finger domain enables XIAP to function as an E3 ubiquitin liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(120 citation statements)
references
References 34 publications
(36 reference statements)
5
112
0
2
Order By: Relevance
“…Previous studies showed that the higher levels of NO· generated by chemicals or by iNOS can induce apoptosis or necrosis (reviewed in references 6 and 36). Higher levels of NO· result in XIAP S-nitrosylation which consequently abolishes XIAP's anticaspase-3 activity (58).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the higher levels of NO· generated by chemicals or by iNOS can induce apoptosis or necrosis (reviewed in references 6 and 36). Higher levels of NO· result in XIAP S-nitrosylation which consequently abolishes XIAP's anticaspase-3 activity (58).…”
Section: Discussionmentioning
confidence: 99%
“…The biotin switch assay for detecting the S-nitrosylation was performed as previously described (Tsang et al, 2009). Adult male mouse brain or HEK 293T cells overexpressing Cdk5 or its cysteine mutants were lysed in HENT buffer (250 mM HEPES, 1 mM EDTA, 0.1 mM neocuproine, 1% Triton X-100).…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical studies suggest that XIAP may be partially associated with the pathogenesis of Parkinson's disease and dementia with Lewy bodies (Kawamoto et al, 2012). Interestingly, XIAP dysfunction resulting from S-nitrosylation has also been described in Parkinson's disease (Tsang et al, 2009). Also, transgenic expression of XIAP in neurons using the neuron-specific enolase promoter (nse-XIAP) improves prognosis in a mouse model of Parkinson's disease (Crocker et al, 2003).…”
mentioning
confidence: 99%